337 Primary imiquimod treatment versus surgery for vulvar intraepithelial neoplasia – PITVIN study. Baseline Results of a Randomized Clinical Trial. (4th December 2020) - Trutnovsky, Gerda; Reich, Olaf; Joura, Elmar A; Ciresa-Koenig, Alexandra; Widschwendter, Andreas; Schauer, Christian; Bogner, Gerhard; Jan, Ziga; Boandl, Angelika; Tamussino, Karl
Abstract : Introduction/Background: Usual type vulvar intraepithelial neoplasia (u-VIN) is a premalignant condition of the squamous epithelium of the vulva caused by persistent infection with high-risk human papillomavirus (HPV), and classified as high grade squamous intraepithelial lesion (HSIL). Surgery is the standard treatment, but recurrences occur in about 50% of patients. Imiquimod, a topical immune response modifier, has been shown to be effective, but has not been compared to surgery. The aim of this study was to compare the effectiveness and acceptance of primary imiquimod treatment with surgical treatment of HSIL/VIN. Methodology: This was a multicentre randomised controlled trial of women with histologically confirmed HSIL/VIN II-III. Exclusion criteria were clinical suspicion of microinvasion, a history of vulvar cancer, severe dermatosis, pregnancy, and any active treatment for VIN within the previous three months. Patients were randomized to primary topical treatment or surgery at a ratio of 1:1 and stratified by unifocal or multifocal disease. Treatment with imiquimod was self-administered for a period of 4 months with possible extension. Surgical treatment was performed according to the standard procedures of the trial site. Clinical assessment, colposcopy, vulvar punch-biopsy and HPV-test (cobas®, Roche) were performed at baseline and 6 months. Clinical follow-up, including questionnaires on health-related quality-of-life, was conducted at 12 months. Results: Between June 2013 and January 2020 a total of 110 patients were enrolled at six hospitals in Austria. Mean age was 51 years (SD 16, range 19 -82) with 57% being postmenopausal. 66 patients (61%) had a history of previous HPV related anogenital HSIL or genital warts, and 21 women (19%) had received previous treatment for VIN. 85 women (78%) presented with unifocal and 24 (22%) with multifocal VIN, and 56 women (51%) reported local symptoms. 40 women (37%) had a history of current or past smoking. 56 women were allocated to primary treatment with imiquimod, and 54 women to primary surgery. Surgical treatment was performed by local excision in 22 cases (14 cold-knife, 6 electrosurgical), by laser destruction (n= 27), or combined (n=3). 12-months follow-up will be completed in January 2021. Conclusion: The results of this clinical trial will show whether imiquimod is a safe and effective alternative to surgery in women with HSIL/VIN2-3. Disclosures: The study was funded by the Austrian Science Fund (FWF) and the Austrian Association for Gynecologic Oncology (AGO). The study medication Aldara 5% cream was provided by Meda Pharma GmbH. The authors have no conflict of interest.